ANALISIS KONTRASTIF AFIKSASI VERBA BAHASA INDONESIA DAN BAHASA INGGRIS PADA KARTUN BERBIE - Jannah, Maftuhatul; Ade Kartika Devi (Jurnal Pesastra (Pendidikan Bahasa dan Sastra), 2024)
This research analyzes cross-language contrasts in the form of verb affixations in Indonesian and English. The data sources used in this research are the Berbie cartoon entitled "Berbie It Takes Two part 1" and the Rainbow Ruby cartoon entitled "Royal Princess Duties". In this research, researchers used qualitative descriptive methods. In this research, the listening method was used with basic tapping techniques and advanced techniques in the form of note-taking techniques. Researchers also use recording techniques by making a list of data from the languages ​​studied, in this context, namely Indonesian and English. Based on the research results, twenty prefix and suffix affixation data were found in Indonesian and English. This research aims to compare the similarities and differences in verb affixation between Indonesian and English in this cartoon film. The similarities between affixation in these two languages ​​are the emergence of new words, modification of meaning, and changes in word categories. Even though these two affixations have differences, in both languages ​​they both have an important role in enriching the vocabulary and enabling the formation of new words that have certain meanings.